THE EFFECT OF USING VIDEO IN LISTENING COMPREHENSION - Zanuba Arifah Khofshoh (FKIP, Universitas Billfath Lamongan, 2022)
The aim of this study were 1) to develop students' listening comprehension by using video materials in the Advanced Listening course and 2) to evaluate students' attitudes towards the use of video materials in learning advanced listening courses. The sample of the student population for this study was 21 third semester students of English Education Study Program of Billfath University. This research was conducted for one semester. One group pretest-posttest design was implemented in this study. The instrument used in this research is a test. The data from the test was then analyzed using the T-Test to determine the T-value. The scores from the pre-test and post-test can be evidence of whether there is an increase in student scores after a study is carried out.